PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN CALISTUNG BAGI MAHASISWA STPAK St. YOHANES RASUL WAENA TAHUN AKADEMIK 2017/2018 - Aleda Mawene; Adolina V. Lefaan (LPPM Uncen, 2018)
Learning process in early grades should be focused on strengthening the competence of leaning, writing, and numeracy (further mentioned as calistung) as a basis to learn other knowledges in higher grades. The learning process in elementary is thematic based so the material of reading, writing and numeracy can be taught in integrated way. This integrated way of calistung requires a right learning media. Therefore, a training of media making for this particular way of learning is given to the seventh semester students of STPAK (Christian Teaching Collage) St. Yohanes Rasul Waena. The goals of this training is to improve the abilities and skills of trainees to make and use a simple media in this particular way of learning in grade 1 to 3. This training is design by following the PAKEM model, supported by the inquiry method, as long as the brainstorming technic, guided training, demonstration and simulation. The results of this training showed that there was an increasing the ability of media making as 56,25%. Also, this training emerged the creativity of trainees in media making based in Papuan Culture with the name “pinojek hitung” (numeracy learning based in the selling process Papuan local fruit ‘pinang’). Keywords: training, calistung media, inquiry, pinojek hitung